Zum Gedenken an Eberhard Schmidhäuser - Institut für Kriminalwissenschaften (Hamburger Universitätsreden Neue Folge, 2004)
The speeches documented here were held at an academic commemoration ceremony at the University of Hamburg on 6 February 2003 in honour of Prof. Eberhard Schmidhäuser.